Organization of Plant Turnaround Maintenance: an Analytical Framework of Generic Processes - Ghazali, Zulkipli (Intellectbase International Consortium, 2011)
Plant turnaround maintenance is a fundamental asset management in capital intensive process-based industries. The successful implementation of turnaround maintenance among others depends on the appropriate provision of institution and organization for the governance of the event. However, it is not uncommon for senior management of these companies to focus their attention on the engineering, business, and economic aspects of the event. This tendency has left several gaps in the knowledge and understanding of the organizational dimensions of this event. To a remarkable degree, it is rare to find literature on organizational characteristics of plant turnaround maintenance. This paper proposes an analytic framework for examining the organizational dimensions of the plant turnaround by describing six core generic processes through the general concepts of institution and organization namely rules, roles, and groups. The generic processes include formation of turnaround maintenance organization, resource mobilization and management, communication, conflict management, contracts management, and relationships with external organizations. The framework provides means for the understanding of turnaround maintenance organization from the social science standpoint that was scarcely addressed in the management circles.